1998
DOI: 10.1021/jp9804143
|View full text |Cite
|
Sign up to set email alerts
|

Underpotential Deposition of Copper on Iodine-Modified Pt(111):  In Situ STM and ex Situ LEED Studies

Abstract: The dynamic process of underpotential deposition (UPD) of copper on iodine-modified Pt(111) electrode in sulfuric acid solution was investigated by in situ scanning tunneling microscopy and ex situ low-energy electron diffraction. Prior to the copper deposition, iodine adlayer structures were characterized by both techniques. It was found that well-ordered iodine adlayers with the structures of (3 × 3) and ( × )R19.1° could be prepared by immersion of the electrode in a solution containing iodide ions unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 30 publications
4
48
0
4
Order By: Relevance
“…The fit of coefficients higher than V ͱ 13G 0 showed that the series eventually converges. Many experimental studies of the I-Pt͑111͒ system show 5,25,26 that there exist two different rigid translational possibilities in the ͑3 ϫ 3͒ cell: sym and asym, both characterized by a perfect hexagonal arrangement inside the unit cell. From our theory, the translational energy Fig.…”
Section: Application Of the Theory To Real Systemsmentioning
confidence: 99%
“…The fit of coefficients higher than V ͱ 13G 0 showed that the series eventually converges. Many experimental studies of the I-Pt͑111͒ system show 5,25,26 that there exist two different rigid translational possibilities in the ͑3 ϫ 3͒ cell: sym and asym, both characterized by a perfect hexagonal arrangement inside the unit cell. From our theory, the translational energy Fig.…”
Section: Application Of the Theory To Real Systemsmentioning
confidence: 99%
“…It is the so-called ͑3 ϫ 3͒-asym structure. [24][25][26][27][28][29][30][31][32][33][34][35][36][37]41,42 We believe that our model based on geometrical principles can also explain the appearance of this particular structure. Note that the arrangement of ͑3 ϫ 3͒-asym iodine adlayer on Pt(111) has been described in many papers, so far.…”
Section: Example Studymentioning
confidence: 99%
“…In case of ͑3 ϫ 3͒-asym, each threefold iodine atoms is surrounded by six neighboring adatoms positioned at a higher level. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] In order to understand the conditions for appearance and differences between ͑3 ϫ 3͒-sym and ͑3 ϫ 3͒-asym structures we employ our model, looking for a full range of possible FIG. 4.…”
Section: Example Studymentioning
confidence: 99%
“…These lattices have been characterized by LEED, [6][7][8][9][10][11][12] ADAM, 13 STM, [14][15][16] and Surface X-ray Scattering ͑SXS͒. [17][18][19][20][21] The same type of iodine adlayer on Pt͑111͒ was found for preparations from gas phase [12][13][14] and from aqueous solution.…”
Section: Introductionmentioning
confidence: 97%
“…[17][18][19][20][21] The same type of iodine adlayer on Pt͑111͒ was found for preparations from gas phase [12][13][14] and from aqueous solution. [6][7][8][9][10][11]15,16 Experimental data also show that an iodine adlayer with ͑3 ϫ 3͒ unit cell structure can form two distinct lattices, 10,[13][14][15][16] in which iodine-iodine interatomic distance ͑4.162 Å͒ and surface coverage are the same, but iodine adatoms possess different registries. They are known as the ͑3 ϫ 3͒-sym and ͑3 ϫ 3͒-asym adlattices.…”
Section: Introductionmentioning
confidence: 99%